The Troll Observing Network (TONe): A contribution to improving observations in the data-sparse region of Dronning Maud Land, Antarctica - Pedersen, Christina A.; Njåstad, Birgit; Aas, Wenche; Darelius, Elin; Descamps, Sébastien; Flått, Stig; Hattermann, Tore; Hudson, Stephen R.; Miloch, Wojciech J.; Rykkje, Simen; Schweitzer, Johannes; Storvold, Rune; et al. (Polar Research, 2024)
Understanding how Antarctica is changing and how these changes influence the rest of the Earth is fundamental to the future robustness of human society. Strengthening our understanding of these changes and their implications requires dedicated, sustained and coordinated observations of key Antarctic indicators. The Troll Observing Network (TONe), now under development, is Norway’s contribution to the global need for sustained, coordinated, complementary and societally relevant observations from Antarctica. When fully implemented within the coming three years, TONe will be a state-of-the-art, multi-platform, multi-disciplinary observing network in data-sparse Dronning Maud Land. A critical part of the network is a data management system that will ensure broad, free access to all TONe data to the international research community.
Section: Perspectives
Keywords: Antarktis; Dronning Maud Land; Sørishavet; Troll forskningsstasjon; biologi; datainnsamling; forskningsinfrastruktur; fysikk; geologi; internasjonal samarbeid; kjemi

International Polar and Geophysical Years - Barr, Susan (Antarctic Resolution, 2021)
Keywords: Antarktis; Det internasjonale geofysiske år (IGY); Det internasjonale polaråret (IPY); forskning; internasjonal samarbeid

Project and Community Management in Polar Sciences – Challenges and Opportunities - Werner, Kirstin; Zaika, Yulia; Pavlov, Alexey K; Lidström, Sven; Pope, Allen; Badhe, Renuka; Brückner, Marlen; Cristini, Luisa (Adv. Geosci., 2019)
Because geoscientific research often occurs via community-instigated bursts of activity with multi-investigator collaborations variously labelled as e.g., years (The International Polar Year IPY), experiments (World Ocean Circulation Experiment WOCE), programs (International Ocean Discovery Program), missions (CRYOSAT spacecraft), or decades (The International Decade of Ocean Exploration IDOE), successful attainment of research goals generally requires skilful scientific project management. In addition to the usual challenges of matching scientific ambitions to limited resources, on-going coordination and specifically project management, planning and implementation of polar science projects often involve many uncertainties caused by, for example, unpredictable weather or ocean and sea ice conditions, large-scale logistical juggling; and often these collaborations are spatially distributed and take place virtually. Large amounts of funding are needed to procure the considerable infrastructure and technical equipment required for polar expeditions; permissions to enter certain regions must be requested; and potential risks for expedition members as well as technical issues in extreme environments need to be considered. All these aspects are challenging for polar science projects, which therefore need a well thought-through program including a realistic alternative “plan B” and possibly also a “plan C” and “plan D”. The four most challenging overarching themes in polar science project management have been identified: international cooperation, interdisciplinarity, infrastructure, and community management. In this paper, we address ongoing challenges and opportunities in polar science project management based on a survey among 199 project and community managers and an additional of 85 project team members active in the field of polar sciences. Case studies and survey results are discussed with the conclusive goal to provide recommendations on how to fully reach the potential of polar sciences project and community management.
Publisher: Copernicus Publications
Keywords: Antarktis; geovitenskap; internasjonal samarbeid; klimaendringer; miljøendringer; polarområdene

The ANTOSTRAT Legacy: Science Collaboration and International Transparency in Potential Marine Mineral Resource Exploitation of Antarctica - Cooper, Alan; Barker, Peter; Barrett, Peter; Behrendt, John; Brancolini, Giuliano; Childs, Jonathan; Escutia, Carlota; Jokat, Wilfried; Kristoffersen, Yngve; Leitchenkov, German; Stagg, Howard; Tanahashi, Manabu; et al. (Science Diplomacy: Antarctica, Science, and the Governance of International Spaces, 2011)
Keywords: Antarktis; geopolitikk; internasjonal samarbeid; marin geologi; mineraler; ressurser; stratigrafi; tektonikk

Guest editorial—the 1959 Antarctic Treaty: reflecting on the 50th anniversary of a landmark agreement - Dodds, Klaus (Polar Research, 2010)
Commemorating a particular anniversary is always an arbitrary affair, an act of whimsy. After all, why acknowledge the 50th anniversary of someone or some event as opposed to the 48th? In terms of birthdays, we tend to celebrate each year as another rite of human passage. However, when it comes to events such as wars and diplomatic encounters, the media and political commentators like more substantial blocks of time: 10th, 25th, 50th, 75th and 100th anniversaries are particularly noteworthy. The year 2009 has proven no different in terms of representing a temporal marker for the 50th anniversary of the signing of the 1959 Antarctic Treaty. In December 2009 a so-called Antarctic Treaty Summit was held in Washington, D.C. to take advantage of not only such a milestone, but also “to highlight lessons learned about international governance ‘with the interests of science and the progress of all mankind’ ” (Antarctic Treaty Summit 2009, emphasis added).
Keywords: Antarktis; Antarktistraktaten; historie; internasjonal samarbeid; politikk

The interplay of global and polar regimes - Young, Oran R. (Polar Research, 1999)
The growing salience of interactions between the functionally broad but geographically narrow regimes for the polar regions and the geographically broad but functionally specific regimes emerging to deal with global environmental changes directs attention to the issue of institutional interplay. Interplay among regimes can cause mutual interference or foster synergy. Adopting a pragmatic stance that assumes no fundamental changes in international society, this essay suggests ways to: (1) adapt global regimes dealing with ozone depletion, climate change and biodiversity to the conditions prevailing in the polar regions; and (2) ensure that concerns arising in the polar regions receive serious consideration in global forums. Specific suggestions range from modest initiatives involving monitoring and assessment to more ambitious initiatives, such as the establishment of a chamber of regions in global regimes.
Keywords: Antarktis; biodiversitet; internasjonal samarbeid; klimaendringer; klimapolitikk; ozonlaget; polarområdene

The political experiment in Antarctica - Sollie, Finn (Bulletin of the Atomic Scientists, 1970)
General discussion of international cooperation in Antarctica. In special issue Antarctica since the IGY; international laboratory for science and diplomacy.
Publisher: Routledge In special issue Antarctica since the IGY; international laboratory for science and diplomacy. Reprinted in Lewis, Richard S. and Smith, Philip S., eds., Frozen future: a prophetic report from Antarctica, New York, 1973.
Keywords: Antarktis; Antarktistraktaten; internasjonal politikk; internasjonal rett; internasjonal samarbeid